OIL POLLUTION ABATEMENT - Wahyudi Wisaksono (Scientific Contributions Oil and Gas, 1987)
To minimize the posibilities of oil pollution, preventive as well as represive action should be consider ed and eventually carried out simultaneousty. Preventive measures are considered in this case for offshore operations. Several repressive methods as well as clean up methods for oil-on-the waters are reviewed. Parameters partinent to the location of the spill related to the methods to be applied should be seriously consi dered.